FACTORS OF STRENGTHENING PSYCHOLOGICAL STABILITY AND SPIRITUAL IMMUNITY IN MILITARY FAMILIES (Universal International Scientific Journal, 2026)
This article scientifically analyzes the main factors of strengthening psychological stability and spiritual immunity in the families of military personnel. In the process of research, the decrees and resolutions of the President of the Republic of Uzbekistan Shavkat Mirziyoyev aimed at strengthening the social protection of military personnel and their family members, improving the spiritual and moral environment were used as a theoretical basis. The article examines the impact of family relations on psychological stability, spiritual education, communication culture, and mechanisms of psychological support provided by the state. The results obtained indicate the need for an integrated approach to increasing psychological immunity in military families
Keywords: military family; psychological stability; spiritual immunity